2005
DOI: 10.1021/bm050071w
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-Coupled Poly(poly(ethylene glycol) monomethacrylate)-Si(111) Hybrids and Their Blood Compatible Surfaces

Abstract: Well-defined (nearly monodispersed) poly(poly(ethylene glycol)monomethacrylate)-Si hybrids were prepared via surface-initiated atom transfer radical polymerization (ATRP) of the poly(ethylene glycol)monomethacrylate (PEGMA) macromonomer on the hydrogen-terminated Si(111) surface (Si-H surface). Both the active chloride groups at the chain ends (from the ATRP process) and the chloride groups converted from some ( approximately 32%) of the -OH groups of the Si-C bonded PEGMA polymer, or P(PEGMA), brushes were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
177
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(180 citation statements)
references
References 59 publications
3
177
0
Order By: Relevance
“…Similarly, Xu et al prepared a series of POEGMA or PHEMA modified silicon surfaces by SI-ATRP and coupled bioactive molecules including collagen (for cell adhesion), heparin (for antithrombogenicity), and IgG (for antigen binding) to the pendant hydroxyl groups by chemically bifunctional molecules such as thionyl chloride, 1,1 0 -carbonyldiimidazole and succinic anhydride. [44][45][46] This strategy also favors a high signal-to-noise ratio in biosensor and microarray applications. Xu et al reported recently on binary brushes of poly(poly(ethylene glycol) methacrylate-co-poly(ethylene glycol)methyl ether methacrylate) (P(PEGMA-co-PEG-MEMA)) and poly(poly(ethylene glycol)methyl ether methacrylate)(PPEGMEMA) prepared by consecutive ATRP from a resist-microdomained silicon wafer surface.…”
Section: Regulation Of Specific Protein/surface Interactions By Surfamentioning
confidence: 99%
“…Similarly, Xu et al prepared a series of POEGMA or PHEMA modified silicon surfaces by SI-ATRP and coupled bioactive molecules including collagen (for cell adhesion), heparin (for antithrombogenicity), and IgG (for antigen binding) to the pendant hydroxyl groups by chemically bifunctional molecules such as thionyl chloride, 1,1 0 -carbonyldiimidazole and succinic anhydride. [44][45][46] This strategy also favors a high signal-to-noise ratio in biosensor and microarray applications. Xu et al reported recently on binary brushes of poly(poly(ethylene glycol) methacrylate-co-poly(ethylene glycol)methyl ether methacrylate) (P(PEGMA-co-PEG-MEMA)) and poly(poly(ethylene glycol)methyl ether methacrylate)(PPEGMEMA) prepared by consecutive ATRP from a resist-microdomained silicon wafer surface.…”
Section: Regulation Of Specific Protein/surface Interactions By Surfamentioning
confidence: 99%
“…1,2 Polymer brushes are particularly suited for covalent immobilization of biomolecules because they possess a well-defined structure, excellent mechanical stability and dense functional groups. 3,4,5,6,7,8,9,10 Moreover, the number of binding sites for biomolecules can be controlled by the polymer chain length. While this concept is particularly successful for planar and inorganic substrates, the decoration of there-dimensional macroporous polymeric substrates with polymer brushes provides a significantly bigger challenge.…”
Section: Introductionmentioning
confidence: 99%
“…A bicinchoninic acid protein assay (MicroBCA) was performed to determine the total amount of protein adsorbed onto the polymer surface from PPP [23]. Prewetted polymer films (12  0.3 mm, diameter  thickness) were incubated in 24-well plates containing 2 ml of PPP at 37°C for 5, 15, 30, 60 and 120 min, respectively.…”
Section: In Vitro Hemocompatibilitymentioning
confidence: 99%
“…Plasma recalcification time and thromboplastin time are two parameters for evaluating the in vitro hemocompatibility of materials [23,26]. When Ca 2+ (factor IV) is complemented to the antico- agulated PPP, prothrombin (factor II) will be activated by the endogenous blood coagulation system and converted to thrombin [30].…”
Section: Hemocompatibility Evaluationmentioning
confidence: 99%